Shikonin mediated anti-acute lung injury and hemostatic effects via inhibiting uPA - Chengcheng Li; Shuru Lu; Chunqi Xu; Baoyuan Huang; Qiumei Wang; Enxin Zhang; Xiaojun Zhang (Journal of Functional Foods, 2023)
Shikonin is the main active ingredient in Arnebiae Radix, an herbal medicine with anti-inflammatory and hemostatic effects, yet which mechanism remains unveiled. Urokinase-type plasminogen activator (uPA) not only regulates fibrinolysis, but also modulates macrophage invasion, matrix remodeling and adhesion. This study examined whether uPA participated in the anti-inflammatory activity of Shikonin on LPS-induced mice acute lung-injury (ALI) and RAW264.7 models, and investigated whether Shikonin mediated a hemostatic effect by inhibiting uPA in animal serum. The results showed that Shikonin ameliorated inflammation and reduced uPA in the lung of ALI mice. Proteomic results revealed that Shikonin markedly decreased uPA, MMP-9 and pro-inflammatory cytokines in macrophages. Besides, Shikonin decreased serum uPA and promoted blood coagulation. Collectively, current data suggested that Shikonin inhibited uPA, which possibly associated with its anti-inflammatory and hemostatic effects.